Improvement of the Training of the Future Specialists in Pharmaceutical Industry on the Basis of the Personally Oriented Teaching - Anatolii Komyshan (Pedagogical Discourse, 2015)
It is determined that the personally oriented teaching is one of the perspectives in modern Ukrainian higher education. On the background of theoretical research it is cocluded that such teaching allows the students to realize their aspirations, directs the students to self-reliant actions, making decisions, abilities to adapt to new life conditions creative thinking, ability to react sufficiently to life’s challenges. The article considers the main organizational and pedagogical conditions of the personally oriented teaching of future specialists in pharmaceutical industry that will improve their level of educational achievement and the development of personal qualities.